Impacts of the COVID-19 pandemic on unmet social needs, self-care, and outcomes among people with diabetes and poor glycemic control. Issue 1 (February 2022) - Patel, Minal R.; Zhang, Guanghao; Leung, Cindy; Song, Peter X.K.; Heisler, Michele; Choe, Hae Mi; Mehdipanah, Roshanak; Shi, Xu; Resnicow, Kenneth; Rajaee, Geila; Piette, John D.
Highlights: High rates of food and housing insecurity were observed for lower income people. A1c levels were lower during the pandemic. Systolic blood pressure increased during pandemic months. The pandemic was associated with more days engaging in physical activity. Abstract: Aims: The purpose of this study was to examine whether pandemic exposure impacted unmet social and diabetes needs, self-care behaviors, and diabetes outcomes in a sample with diabetes and poor glycemic control. Methods: This was a cross-sectional analysis of participants with diabetes and poor glycemic control in an ongoing trial (n = 353). We compared the prevalence of unmet needs, self-care behaviors, and diabetes outcomes in successive cohorts of enrollees surveyed pre-pandemic (prior to March 11, 2020, n = 182), in the early stages of the pandemic (May–September, 2020, n = 75), and later (September 2020–January 2021, n = 96) stratified by income and gender. Adjusted multivariable regression models were used to examine trends. Results: More participants with low income reported food insecurity (70% vs. 83%, p < 0.05) and needs related to access to blood glucose supplies (19% vs. 67%, p < 0.05) during the pandemic compared to pre-pandemic levels. In adjusted models among people with low incomes, the odds of housing insecurity increased among participants during the early pandemic months compared with participants pre-pandemic (OR 20.2 [95% CI 2.8–145.2], p < 0.01). A1c levels were better among participants later in the pandemic than those pre-pandemic (β = −1.1 [95% CI −1.8 to −0.4], p < 0.01), but systolic blood pressure control was substantially worse (β = 11.5 [95% CI 4.2–18.8, p < 0.001). Conclusion: Adults with low-incomes and diabetes were most impacted by the pandemic. A1c may not fully capture challenges that people with diabetes are facing to manage their condition; systolic blood pressures may have worsened and problems with self-care may forebode longer-term challenges in diabetes control.